Development and Characterization of a Hydrogel Containing Chloramphenicol-Loaded Binary Ethosomes for Effective Transdermal Permeation and Treatment Acne in Rat Model - Liu RJ; Li M; Zhu Q; Liu HY; Zhang XX; Han XY; Yu MJ; Zhou JW; Han CY (International Journal of Nanomedicine)
Run jia Liu,1 Miao Li,1 Qian Zhu,1 Hui ying Liu,1 Xing xiu Zhang,1 Xiang yuan Han,1 Meng jun Yu,1 Jian wen Zhou,2 Cui yan Han1 1School of Pharmacy, Qiqihar Medical University, Qiqihar, People’s Republic of China; 2Institute of Medicine and Drug Research, Qiqihar Medical University, Qiqihar, People’s Republic of ChinaCorrespondence: Cui yan Han, School of Pharmacy, Qiqihar Medical University, Qiqihar, People’s Republic of China, Tel/Fax +86-24-2663822, Email hcymuphar@qmu.edu.cnPurpose: Acne is a serious disfiguring follicular sebaceous gland disorder that negatively affects patients’ quality of life and self-image. Chloramphenicol (CAM) is effective against Propionibacterium acnes and Staphylococcus aureus which cause acne, often used as a hospital preparation for acne treatment. However, because of its toxicity and poor water solubility, its use has been restricted. To overcome these limitations, the study focused on developing CAM-loaded binary ethosomes (CAM-BE) and incorporating them into a hydrogel system for transdermal delivery.Methods: CAM-BE were prepared and characterized. Following incorporation of the selected formulation into the hydrogel, the formulation’s skin-interaction was evaluated using attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy and confocal laser scanning microscopy (CLSM). Furthermore, a rat ear acne model was used to evaluate the formulation’s in vivo anti-inflammatory efficacy and ex vivo skin permeability.Results: The optimal formulation contained ethanol/propylene glycol ratios of 3:7 (w/w), exhibited particle size was 97.68 ± 4.9 nm, zeta-potential was − 23.5 ± 1.3 mV, and encapsulation efficiency was 60.36 ± 2.12%. The BE hydrogel that was created showed persistent drug release. Additionally, it demonstrated an enhanced flow of 4.374 ± 0.12 μg/cm2/hour, permeability coefficient was 3.65 ± 0.09 cm/h× 10− 3, and apparent skin deposition was 17.77 ± 1.13 μg/cm2. CLSM and ATR-FTIR confirm that loading CAM into a binary ethosomes enables drugs to pass more easily through the stratum corneum. In vivo testing and histopathological analysis demonstrated that the CAM-BE hydrogel significantly inhibited swelling in the rat auricle, compared to both the free CAM hydrogel and adapalene hydrogel.Conclusion: With their strong anti-inflammatory properties and improved skin penetration, binary ethosomes could be a viable new CAM delivery method. The new formulation was therefore seen as quite promising. Keywords: acne, binary ethosomes, chloramphenicol, ex vivo permeation, transdermal delivery